Dialysotherapy effect on the quality of life for renal patients - Kułakowska, Aleksandra; Kuc, Monika; Lepczyński, Bartłomiej; Kłakowicz, Philip; Lechowski, Sebastian (Journal of Education, Health and Sport, 2023)
The purpose of this essay is to examine how dialysis treatment affects patients’ quality of life at the Department of Nephrology. The course of chronic renal disease and its management greatly influence the standard of living for dialysis patients. Renal insufficiency consequently results in numerous restrictions on patients’ social, intellectual, and physical activities. Patients with chronic kidney disease have longer lifespans thanks to renal replacement therapy.